2001
DOI: 10.1016/s0010-9452(08)70576-8
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Grammatical Gender in Normal and Aphasic Speakers of Russian

Abstract: Sensitivity to grammatical gender was investigated in 22 Russian-speaking aphasic patients, compared with young controls. Experiment 1 used a cued shadowing paradigm to assess gender priming (facilitation and/or inhibition of lexical access by a prenominal modifier with congruent, incongruent or neutral gender). Experiment 2 used a grammaticality judgment paradigm with similar stimuli. Normals showed significant interactions between gender and priming in Experiment 1 (facilitation for feminine and neuter nouns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
(30 reference statements)
0
24
0
Order By: Relevance
“…Evidence for gender priming comes from the previous studies of language production [e.g. Akhutina et al, 2001;Deutsch et al, 1999;Schriefers et al, 1998] and comprehension [e.g. Boelte and Connine, 2004;Colé and Segui, 1994;Friederici and Jacobsen, 1999;Grosjean et al, 1994;Hartmann, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for gender priming comes from the previous studies of language production [e.g. Akhutina et al, 2001;Deutsch et al, 1999;Schriefers et al, 1998] and comprehension [e.g. Boelte and Connine, 2004;Colé and Segui, 1994;Friederici and Jacobsen, 1999;Grosjean et al, 1994;Hartmann, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…The agrammatic participants in this study had difficulties rejecting these ungrammatical sentences, in comparison to the control subjects. Several studies show that Slavic-speaking agrammatic aphasics are sensitive to the morphology of case and gender agreement, and transitive verb subcategorization (Akhutina et al, 2001;Lukatela, Crain, & Shankweiler, 1988;Milekic et al, 1995;Smith & Bates, 1987; but see Luria, 1975 for findings on difficulties in grammaticality judgment of sentences with ungrammaticality is related to case agreement, tense and gender). Smith and Mimica (1984) tested the role of morphosyntactic cues in agrammatic comprehension, and found that although speakers of Serbo-Croatian with agrammatism are relatively sensitive to case morphology, their ability to use these cues for comprehension is poorer than that of the control participants.…”
Section: Movement and Morphology In Agrammatism In Slavic Languagesmentioning
confidence: 99%
“…Gender mismatches and matches lend themselves to rather easy experimental testing which could be conducted even with young children. It would be particularly beneficial to conduct experiments on the acquisition of gender given some recent work on gender processing in Russian (Ahutina et al 2001;Taraban, Kempe 1999). In the former work, we showed that Russian listeners can exploit gender agreement cues on-line, helping them to predict the identity of an upcoming word.…”
Section: Acquisition Of Nominal Categoriesmentioning
confidence: 99%